Hybrid nano-jet impingement cooling of a curved elastic hot surface under the combined effects of non-uniform magnetic field and upper plate inclination - Selimefendigil, Fatih; Öztop, Hakan Fehmi (Elsevier, 2022)
In this study, slot hybrid nano-jet impingement cooling application of a curved elastic surface is considered under the combined effects of non-uniform magnetic field and upper plate inclinations. When magnetic field is present, the local Nusselt number (Nu) peaks are suppressed, but in absence of magnetic field, profound rise of stagnation point Nu is seen with higher Re. The increment amount of the local peak Nu becomes 155.5% and 50.5% at Ha=0 and Ha=20. Significant variations of the local peak Nu locations are obtained when elastic modulus are varied with magnetic field at the highest strength. There is 141% variation of average Nu for the curved elastic part when walls with the lowest and highest elastic modulus cases are compared. There is 7% variations in the average Nu when the amplitude of the magnetic field is varied. The left and right plate inclinations contributed differently to the overall convective cooling performance due to the non-uniform magnetic field effects. Non-uniform magnetic field parameters along with the plate inclinations can be used for cooling performance of confined slot jet impingement system for a surface with curved elastic part.
Keywords: Slot jet impingement; Non-uniform magnetic field; Upper plate inclinations; Elastic wall; Finite element method; Hybrid nanofluid